DESIGNING THE PESANTREN CURRICULUM TO COUNTER RADICALISM: Study on Pondok Pesantren Wali Songo Ngabar Ponorogo - Suradi, Ahmad; Khoiri, Qolbi; Nilawati, Nilawati; Gustari, Nopian (ULUL ALBAB Jurnal Studi Islam, 2021)
This study aims to describe the moderate educational views of the Pondok Pesantren Wali Songo community in Ngabar Ponorogo and their efforts to prevent radical ideology. This is a qualitative research and the subject is the main source of data. The informants are the Kyai (the leader) and the Asâtîdh (the teachers) Council in the Pesantren. The results reveals that the Pesantren Wali Songo designed a curriculum that provided a comprehensive understanding of Islamic teachings. For example, the material of fiqh is embedded with uṣûl al-fiqh. In uṣûl al-fiqh, there are rules of istinbâṭ al-ḥukm besides the Quran and hadith such as ijmâ‘, qiyâs, ‘urf, maṣlaḥah al-mursalah, and maqâsid al-sharî‘ah so that fiqh is flexible. In addition, the Pesantren recruited a board of teachers who had moderate understanding and background in kâffah Islamic ideology. Santri (the students) are protected from information access and certain association  which lead to radicalism. In developing moderate Islam, the curriculum there require them to study books that explain the understanding of Islam Ahl al-Sunnah wa al-Jamâ‘ah.